2014
DOI: 10.1021/jp505482p
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemical Heterogeneity on the Accuracy of Pore Size Distributions in Disordered Solids

Abstract: Disordered porous solids, such as heterogeneous catalysts, possess internal void spaces with high degrees of both chemical and geometric heterogeneity. For pore size distributions (PSDs) to be useful void space descriptors for aiding understanding of phenomena such as catalyst activity, their level of accuracy must be known. Due to differences in specific interactions and wetting behavior, the choice of adsorbate can severely impact the accuracy of PSDs derived for disordered materials using gas sorption. Wett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(102 reference statements)
3
8
0
Order By: Relevance
“…This is just what was observed for nitrogen and argon adsorption for sol-gel silicas in previous work [8].…”
Section: Integrated Experiments and Surface Wetting Effectssupporting
confidence: 86%
See 2 more Smart Citations
“…This is just what was observed for nitrogen and argon adsorption for sol-gel silicas in previous work [8].…”
Section: Integrated Experiments and Surface Wetting Effectssupporting
confidence: 86%
“…In previous work [8] it was found that, while the surface fractal dimension obtained from the adsorption isotherm declined following mercury entrapment in a mesoporous silica when nitrogen was used as the adsorbate, there was no such significant change in fractal dimension when argon was used as the adsorbate. It was suggested that this effect occurred because nitrogen wetted the smooth mercury metal surface significantly more than argon.…”
Section: Integrated Experiments and Surface Wetting Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, these shortcomings can be considerable, as the interpretation of adsorption measurements using nitrogen or other probes, as well as (mercury) porosimetry, again requires a model, which involves modeling assumptions as well. The interpretation of porosimetry measurements is a mathematical "inverse problem", thus inferring a pore size distribution and the pore connectivity is far from easy for a material with limited additional information on the pore shape [320,[345][346][347][348][349][350][351][352][353][354][355]. The danger in this is conflicting or circular argumentations.…”
Section: Pore Network Modelsmentioning
confidence: 99%
“…On heterogeneous polar surfaces, such as silica, the most commonly used adsorptive, nitrogen, can show some specific adsorption because the nitrogen molecule quadrupole moment is preferentially attracted to polar adsorption sites, such as ions and hydroxyl groups [4]. In previous work, the surface fractal dimensions for a range of controlled pore glasses, and sol-gel and fumed silicas, were obtained by two sets of completely independent physical processes and theories for data analysis, where the first was gas adsorption and the fractal BET model, and the second was small-angle X-ray scattering (SAXS) and Porod analysis [3,7]. It was found that, while argon and butane adsorption gave fractal dimensions that agreed with SAXS measurements, thereby mutually validating each result, the fractal dimension obtained from nitrogen adsorption tended to be always larger than that from SAXS.…”
Section: Introductionmentioning
confidence: 99%